Adiponectin improves endothelial function in mesenteric arteries of rats fed a high-fat diet: role of perivascular adipose tissue - Sena, Cristina (2017)
BACKGROUND AND PURPOSE Adiponectin, the most abundant peptide secreted by adipocytes, is involved in the regulation of energy metabolism and vascular physiology. Here, we have investigated the effects of exogenous administration of adiponectin on metabolism, vascular reactivity and perivascular adipose tissue (PVAT) of mesenteric arteries in Wistar rats fed a high-fat diet. EXPERIMENTAL APPROACH The effects of adiponectin on NO-dependent and independent vasorelaxation were investigated in isolated mesenteric arteries from 12-month-old male Wistar rats (W12m) fed a high-fat diet (HFD) for 4 months and compared with those from age-matched rats given a control diet. Adiponectin ((96 μg·day 1) was administered by continuous infusion with a minipump, implanted subcutaneously, for 28 days. KEY RESULTS Chronic adiponectin treatment reduced body weight, total cholesterol, free fatty acids, fasting glucose and area under the curve of intraperitoneal glucose tolerance test, compared with HFD rats. It also normalized NO-dependent vasorelaxation increasing endothelial NO synthase (eNOS) phosphorylation in mesenteric arteries of HFD rats. In PVAT from aged (W12m) and HFD rats there was increased expression of chemokines and pro-inflammatory adipokines, the latter being important contributors to endothelial dysfunction. Infusion of adiponectin reduced these changes. CONCLUSIONS AND IMPLICATIONS Adiponectin normalized endothelial cell function by a mechanism that involved increased eNOS phoshorylation and decreased PVAT inflammation. Detailed characterization of the adiponectin signalling pathway in the vasculature and perivascular fat is likely to provide novel approaches to the management of atherosclerosis and metabolic disease.